Telehealth interventions on pain in postoperative orthopedic surgery patients: A systematic review - Qothrunnadaa, Azka; Abidah, Aqmarina; Tisel, Yulmira Maria; Tabik, Albertina Dete; Dewi, Yulis Setiya; Mariyanti, Herdina (Institute of Computer Science (IOCS), 2025)
This systematic review evaluates the effectiveness of telehealth interventions in managing pain among postoperative orthopedic surgery patients. The introduction highlights the transformative potential of digital health technologies, such as telemedicine and mobile health applications, in improving access, quality, and efficiency of healthcare, particularly for pain management and patient adherence. The methods section outlines a structured literature search across Scopus, PubMed, and Proquest databases, adhering to PRISMA guidelines, with inclusion criteria focusing on randomized controlled trials (RCTs) and quasi-experimental studies involving adult orthopedic patients aged 18–60 years. Ten studies met the criteria, demonstrating varied telehealth approaches, including mobile apps, video consultations, and remote monitoring. Results indicate significant pain reduction and improved clinical outcomes in telehealth groups compared to standard care, with enhanced patient adherence, functional recovery, and reduced opioid use. However, variability in intervention duration and pain measurement tools underscores the need for standardization. The conclusion affirms telehealth as a valuable tool for postoperative pain management, emphasizing its role in education, monitoring, and psychosocial support. Future research should explore combined interventions and economic impacts to optimize implementation.